Replacement of maize by different levels of triticale on performances and meat yield characteristics of broiler chickens (International Journal of Natural Sciences, 2011)
An experiment was conducted for a period of 5 weeks with 240 day-old cobb-500 broiler chicks and were allocated into six dietary treatments with isocaloric and isonitrogenous containing 2975 Kcal ME/kg DM & 21.70% CP and 3077 Kcal ME/kg DM & 20.34% CP both starter and finisher ration respectively. There were 40 chicks per treatment, each treatment had 4 replication having 10 chicks in each. The dietary treatments were T1 (0% triticale + 100% maize), T2 (20% triticale + 80% maize), T3 (40% triticale + 60% maize), T4 (60% triticale + 40% maize), T5 (80% triticale + 20% maize) and T6 (100% triticale + 0% maize). The broilers of all treatment groups were supplied feeds and water ad libitum throughout the experimental period. There were no significant differences (P>0.05) in feed intake, final body weight, total gain, feed conversion efficiency, survivability% but feed cost per kg live broiler production was differed significantly (P